Conceptual Fields and Magnetic Field: a theoretical model for epistemological classification of tasks in magnetostatics - Glauco Cohen Ferreira Pantoja (Investigações em Ensino de Ciências, 2021)
This work presents a theoretical model for epistemological classification of tasks in magnetostatics aimed at High School and Higher Education. The approach is based on the theory of conceptual fields and includes classification in terms of thought operations necessary to solve the tasks and in these situations’ parameters. Four primary classes of situations are proposed, namely, description of magnetic interactions, analogic symbolization of magnetic fields, non-analogic symbolization of magnetic fields and calculation of magnetic fields. These classes cannot be reduced one to another, however they can occur simultaneously in the same task. Each one was subdivided in secondary classes of situations based on parameters they can assume and ordered by epistemological complexity. As contributions for physics teaching research this work offers a theoretical-methodological model for analyzing students’ progression in the conceptual field of magnetostatics, a conceptual structure for building situations based on predicative and operational competences for understanding the concept of magnetic field, and a practical example of epistemological classification of situations that can be adapted for other areas of Science like Quantum Mechanics, for example.